TEACHER’S CHALLENGES IN TEACHING ENGLISH AT PANJURA PRIVATE SENIOR HIGH SCHOOL IN MALANG - Fajar Wirawan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Challenges of English teacher in learning process and the way of teacher solved the challenges in teaching process, planning process, teaching implementation, and evaluation remain relatively unexplored in the context of Indonesia Private Senior High School where teaching English is one of the lesson most demanding and a difficult job. This study attempted to identify the teacher’s challenges and to explore how the English teacher solves with the challenges in teaching English at Panjura Private Senior High School in Malang. In this study uses qualitative method where one of English teacher becomes participant. Interview and observation are used in this study as the instruments to collect the data. The findings showed that the teacher gets some challenges in teaching English. through a non-participant observation and structured interview with the English teacher who taught English in English class, it was found that there were four kinds of teacher’s challenges in teaching English: (1) The teacher could not control the classroom and manage time, (2) The teacher could not choose appropriate media, (3) The teacher could not assess the students' development, (4) The teacher could not choose the appropriate method. Through an interview showed that the teacher had solution to solve the challenges in teaching English. They were (1) the teacher should apply self-discipline, use polite language, and encourage enthusiasm, (2) the teacher should prepare the media based on the teaching goals and its benefits, (3) the teacher should do an individual approach, give more attention to students, and be creative in teaching, (4) the teacher should be able to determine the suitable teaching methods. Eventually, the implications of this study are identified that the teacher should be able to confront the challenges and be creative in the teaching process. The teacher should be able to realize the needs of students in the situation and create own solutions if the teacher gets the challenged in the English class.